The Investment in the Information Technology and Supply Chain Operational Performance: Mediating Role of Supply Chain Capabilities - Anchalee Hiranphaet; Tommanee Sooksai; Kraiwit Sinthukhammoon; Sarawut Putnuan (International Journal of Supply Chain Management, 2020)
The main purpose of the current study is to examine the impact of the investment on the information technology on the supply chain operational performance. Additionally, the study has examined the mediating role of supply chain capabilities namely the relational capability, IT capability and organizational culture is examined in the relationship between information technology and the supply chain operational performance. Meanwhile, research designed for discovering sources of IT productivity paradox are expected to influence and offer implications for Indonesian companies as well as for other developing economies, who strive for creating business value of IT. The data is collected from the Indonesian manufacturing firms and the response rate for survey was obtained as 75.1%. The SEM-PLS is employed in the study to examine the relationship between and among the variables. IT capabilities are identified as critical for enhancing supply chain performance and also one of the major factors of Supply chain management. The significance of IT and SCM are the widely studied areas, and we also found some studies that investigated supply chain capability as a mediator in context to IT influencing supply chain operational performance. SCC have also been identified as the organizational ability to coordinate SC processes, and be responsive against requests of SC partners and consumer needs and share information resources